Bachelor´s degree in geography and land planning: Contrastivity of the practicum and bachelor thesis - Cejudo Mejías, Vanesa; Oliva Marañón, Carlos (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Geography, coined as a word by Eratosthenes of Cyrene, has been configured as a science since the 19th century The objectives of this research are to carry out a contrastive analysis of the teaching load in credits ECTS of the practicum and bachelor thesis distributed both in the Degree in Geography and in the Degree in Geography and Territory Planning in Spanish Universities. A comparison has been made by ¨ECTS¨ credits, courses and semesters. The results verify the homogeneity regarding the Practicum distributed in 6 ECTS credits and the relative heterogeneity of the bachelor thesis.